2003
DOI: 10.1097/01.sla.0000098624.04100.b1
|View full text |Cite
|
Sign up to set email alerts
|

Cervical or Thoracic Anastomosis After Esophageal Resection and Gastric Tube Reconstruction

Abstract: When performed in a standardized way, neck and chest anastomoses after esophageal resection are equally safe. The additional esophageal resection of 5 cm in the neck group did not increase tumor removal and survival; on the other hand, it did not adversely influence morbidity, anastomotic diameter, or eating as reflected by body weight development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
68
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 211 publications
(73 citation statements)
references
References 35 publications
2
68
0
1
Order By: Relevance
“…Another study was identified as a duplicate report in a non-English language journal [6]. A total of 4 randomized trials were included for the systematic review (table 1)[7,8,9,10]. These studies involved 267 patients, of which 132 patients were randomized for a cervical anastomosis and 135 patients had a thoracic anastomosis (table 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Another study was identified as a duplicate report in a non-English language journal [6]. A total of 4 randomized trials were included for the systematic review (table 1)[7,8,9,10]. These studies involved 267 patients, of which 132 patients were randomized for a cervical anastomosis and 135 patients had a thoracic anastomosis (table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Walther et al [7 ]excluded 47 patients. Seventeen patients had a nonresectable tumor, of which 3 underwent a bypass procedure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Al comparar las técnicas utilizadas, se encontraron diferencias significativas según la localización de la anastomosis (cuello o tórax), pero no en la frecuencia de las complicaciones. Estos hallazgos son similares a los de Walther, et al, en 83 pacientes (41 en cuello y 42 en tó-rax); ambos procedimientos fueron igualmente seguros, con tasas similares de complicaciones y de fugas de la anastomosis; además, no se encontró una diferencia significativa en el tiempo de supervivencia relacionada con el tejido esofágico extra resecado 22 . Los hallazgos de un metaanálisis de Biere, et al, sugieren que la anastomosis cervical podría asociarse con una mayor frecuencia de fugas de la anastomosis y una mayor disminución del flujo vascular del tubo gástrico, asociados a lesiones por contigüidad más frecuentes del nervio recurrente 23 .…”
Section: Discussionunclassified
“…There are several ways to perform esophagectomy generally divided into two groups of transthoracic and transhiatal (3). The question regarding which method of esophagectomy provides better prognosis in patients with esophageal cancer has created debates (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%